Integrasi Bimbingan Konseling dengan Mata Pelajaran Pendidikan Agama Islam di SMK PGRI Cikoneng Kabupaten Ciamis - Melati, Siti; Herlina, N. Hani (Tsamratul Fikri | Jurnal Studi Islam, 2017)
This study aims to find out the concept and implementation of guidance and counseling integration with the subject of Islamic education in SMK PGRI Cikoneng Ciamis Regency. The results show that the integration of general and religious knowledge can be done through four dimensions, namely conceptual, institutional, operational, and architectural dimensions. Implementation of integration counseling guidance with Islamic education is done by emphasizing the position of religion as the guidance of life, solving problems with religious approach, carrying out counseling guidance with Islamic ritual approach